2015
DOI: 10.15408/es.v7i1.1396
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pembelajaran Model Advance Organizer Terhadap Hasil Belajar Biologi Siswa Pada Konsep Protista

Abstract: This study aims to determine the effect of advanced organizer learning model using concept mapping on student's physics learning achievement SMA Negeri 1 Lingsar. This research type is quasi experiment with pretest-posttest control group design. The population of this study is all students of class XI IPA SMA Negeri 1 Lingsar with sampling technique using purposive sampling. The classes that sampled are class XI IPA 2 as experiment class and class XI IPA 1 as control class. The results of study are learning ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
2
0
3
Order By: Relevance
“…In addition, the material protists are also quite a lot so that students are challenging to remember all the material. Shabania et al (2015) explained that protist material is abstract because the object studied is microscopic, so students find it challenging to learn it. Furthermore, Sudarman (2007) stated that the learning process still prioritizes remembering a subject matter.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the material protists are also quite a lot so that students are challenging to remember all the material. Shabania et al (2015) explained that protist material is abstract because the object studied is microscopic, so students find it challenging to learn it. Furthermore, Sudarman (2007) stated that the learning process still prioritizes remembering a subject matter.…”
Section: Methodsmentioning
confidence: 99%
“…Role-Playing has been used worldwide in many fields and purposes. Khaerani (2010) used Role Play for trainees of SMP Muhammadiyah Tangerang to know the influence of role Playing on the learning result of Biology trainees' in-plant movement. From the result, it is concluded that utilizing Role-Playing significantly influences the learning result of Biology trainees.…”
Section: H Research Findingsmentioning
confidence: 99%
“…implementasi kegiatan pembelajaran model advance organizermempunyai efek terhadap hasil belajar, seperti yang sudah diungkap oleh peneliti sebelumnya yaitu Atomatofa, (2013); Kapri, (2017); Parjayanti & Wardono, (2013); Putra, Widyawati, Asyhari, & Putra (2018); Shabania, Mardiati, & Sofyan (2015). Penelitan yang sudah dilakukan oleh para penelititersebut terbukti mampu meningkatkan hasil belajar siswa, namun peneliti merasa tertarik untuk meneliti kembali dengan mempertimbangkan aspek kemampuan pemahaman relasional melalui pendekatan pembelajaran humanistik.Tujuan peneliti adalah berusaha untuk mengembangkan perangkat pembelajaran model advance organizer yang dikembangkan melalui pendekatan humanistik, menitik beratkan pada siswa sebagai objek utama pembelajaran dengan konsep memanusiakan manusia untuk meningkatkan kemampuan pemahaman relasional.…”
Section: Dalamunclassified